MAPPING THE HOUSING AFFORDABILITY IN BEKASI CITY - Asma Rosyidah; Salma Nur Afifah; Shalim Tehupelasury; Agustinus Adib Abadi (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2022)
High urban population growth increases the housing demand and housing prices due to its limitations. These increasing urban housing prices affect housing affordability, especially for urban families with low and medium incomes. If people could buy a house with a large area in the past, now they need years to save money to buy a house with a smaller plot area. This study aims to study the level of housing affordability in Bekasi City based on current property prices. This study uses a quantitative descriptive method with three stages of analysis, namely property price analysis based on location, purchasing power analysis, and affordability analysis of house prices in Bekasi City. For buildings area up to 60m2, the price ranges from 350 to 800 million rupiahs, while the house purchasing power is less than 2.5 million per month. This research shows that most of the residents of Bekasi City cannot afford housing prices not only because of high land prices but rather its location.